2009
DOI: 10.1212/wnl.0b013e3181a82634
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal pattern of regional brain volume change differentiates normal aging from MCI

Abstract: Although age-related regional volume loss is apparent and widespread in nondemented individuals, mild cognitive impairment is associated with a unique pattern of structural vulnerability reflected in differential volume loss in specific regions. Early identification of patterns of abnormality is of fundamental importance for detecting disease onset and tracking progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
366
8
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 465 publications
(428 citation statements)
references
References 30 publications
51
366
8
3
Order By: Relevance
“…The frontal negativity of the classic SW has also been reported to be absent in an older group (Pfefferbaum et al, 1980). This type of topographic finding has been interpreted increasingly as evidence for compensatory frontal activity in older compared with younger subjects, used to maintain relatively high performance levels (e.g., Hong et al, 2014;Hsieh and Fang, 2012;Staub et al, 2014;Vallesi, 2011) in the context of reductions in frontal brain volume (Driscoll et al, 2009;Raz et al, 2005).…”
Section: Fig 1 About Herementioning
confidence: 96%
“…The frontal negativity of the classic SW has also been reported to be absent in an older group (Pfefferbaum et al, 1980). This type of topographic finding has been interpreted increasingly as evidence for compensatory frontal activity in older compared with younger subjects, used to maintain relatively high performance levels (e.g., Hong et al, 2014;Hsieh and Fang, 2012;Staub et al, 2014;Vallesi, 2011) in the context of reductions in frontal brain volume (Driscoll et al, 2009;Raz et al, 2005).…”
Section: Fig 1 About Herementioning
confidence: 96%
“…Finally, while a full review of sex differences in age-related brain change is beyond the scope of this review, it is important to note that the majority of published reports (whether cross-sectional or longitudinal) and across both global and regional measures, show a steeper and more rapid trajectory of decline for males than females [e.g. 3,19,20,24,[25][26][27] Regional changes. The earliest in vivo imaging studies reported global, or non-specific, brain changes in late life [28].…”
Section: Global and Regional Changesmentioning
confidence: 99%
“…The computer-assisted methodology was validated against manual segmentation by an experienced expert 6 and used by other cohorts. [7][8][9][10] Supratentorial brain tissue was classified as normal or abnormal (ischemic) gray or white matter and assigned to 1 of 92 anatomical ROIs of the cerebrum. 6,7 ROIs were organized in an anatomically hierarchical system with 8 ROIs used for this analysis: total brain, frontal lobe, and hippocampus volumes; total lesion, white matter lesion, gray matter lesion, and basal ganglia lesion volumes; and ventricular CSF volumes.…”
Section: Design Of the Whi Ht Trials And Whimsmentioning
confidence: 99%